O Efeito da energia de compactação em propriedades dos solos utilizados na pavimentação do Estado do Ceará - Souza Junior, Joacy Demétrio de (2005)
In 1994, The Department of Constructions, Highways and Transportation of the State of Ceará (DERT/CE) regulated a new compaction energy, denoted intermodified, as an alternative to the regular compaction energ y used in paving engineering. The use of this energy has been largely discussed by road technicians of Ceará, with respect to the effectiveness of its application to some construction materials. The main objective of this work is to evaluate the effect of different compaction energies (intermediary, intermodified and modified) in some geotechnical properties used in paviment engineering. For definition of samples for laboratory tests, a survey in 118 DERT projects files was performed, consisting of 494 gran ular soil deposits distributed all over the State of Ceará. Then, based on the analysis of the geotechnical parameters of the materials, 11 soil samples were collected from the Barreto- Aracatiara section (Road CE- 085) in order to perform classification andgranulometry analysis, as well as compaction, CBR, swelling and resilience tests. The results obtained from laboratory investigations had shown that the CBR values increased substantially as the compaction energy increase, as opposed to the resilient modu lus values, which had not experienced significant changes when submitted to the different investigated compaction energies.